Innovation As a Mediator in The Influence of Transformational Leadership and Digital Technology on Sustainability Performance - Rahma, Wanda; Ariesta Utha, Maria; Mihalay, Albert; Kurniawati, Kurniawati; Hermawan, Asep (Cv. Syntax Corporation Indonesia, 2025)
This study aims to examine the relationship between transformational leadership and digital technology on sustainability performance, mediated by innovation. Data analysis used the Structural Equation Model (SEM) method with SmartPls. Respondents numbered 180 people, obtained through a questionnaire distributed using Google Forms in PT. Adaro Energy Indonesia. The results showed that Transformational Leadership and Digital Technology have an effect on Sustainable Performance and Innovation. However, innovation does not have an effect on Sustainable Performance. Innovation also does not mediate the relationship between Transformational Leadership and Digital Technology on Sustainability Performance. Transformational leadership motivates and empowers employees, drives innovation and change that focuses on long-term goals, and in stills a vision that considers social, environmental, and economic aspects in a sustainable manner. This increases employee commitment and quality of work so that organizational performance can be maintained in the long term.